The clinical use of Alzheimer’s disease biomarkers in patients with mild cognitive impairment: a European Alzheimer’s disease consortium survey - Caprioglio, Camilla; Garibotto, Valentina; Jessen, Frank; Frölich, Lutz; Allali, Gilles; Assal, Frédéric; Frisoni, Giovanni B.; Altomare, Daniele (Journal of Alzheimer's disease, 2022)
Background: Recent advances occurred in the field of Alzheimer’s disease (AD) biomarkers and the introduction of a research framework grounded on a biomarker-based definition of AD might have fostered an increased clinical use of AD biomarkers. Objective: To investigate the clinical use of the main AD biomarkers in patients with mild cognitive impairment (MCI) by examining the beliefs and preferences of professionals (clinicians and biomarker experts) of the European Alzheimer’s Disease Consortium (EADC). Methods: 150 professionals filled in an online survey from May to September 2020. The investigated biomarkers were medial temporal lobe atrophy score (MTA) on structural MRI, typical AD (i.e., temporoparietal and posterior cingulate) hypometabolism on FDG-PET, CSF (Aβ42, p-tau, t-tau), amyloid-PET and tau-PET. Results: The frequency of responders reporting a frequent-to-constant use of MTA (77%) is higher than that of those reporting a frequent-to-constant use of the other AD biomarkers (i.e., CSF: 45%, p=0.014; FDG-PET: 32%, p<0.001; amyloid-PET: 8%, p<0.001; and tau-PET: 2%, p<0.001). CSF is considered the most valuable biomarker in terms of additional diagnostic value, followed by amyloid-PET, tau-PET, and typical AD hypometabolism on FDG-PET. Conclusion: AD biomarkers are widely used across European memory clinics with a clinical research background for the diagnosis of MCI. Overall, we observed that CSF is currently considered as the most useful biomarker, followed by amyloid-PET.
Gesehen am 03.06.2024